CORRELATION AND PATH COEFFICIENT ANALYSIS OF YIELD AND ITS ATTRIBUTING TRAITS IN TOSSA JUTE (CORCHORUS OLITORIUS L.) - ASHUTOSH SAWARKAR; SONIKA YUMNAM; S.G. PATIL; S. MUKHERJEE (The Bioscan, 2014)
The genetic variability, heritability, genetic advance, correlation coefficient and path analysis were estimated for yield and its attributing traits in thirty genotypes of tossa jute (Corchorus olitorius L.). The analysis of variance showed significant differences among the genotypes for all the characters. The highest genotypic variance was for plant height (680.97) followed by green weight (123.59), stick weight (49.33), days to 50% flowering (12.05), fibre weight (1.31), base diameter (0.02) and the lowest genotypic variance was that of bark thickness (0.03). High values of heritability(>90%) were recorded for almost all characters like plant height (93.01%), bark thickness(98.33%), base diameter(94.82%), green weight (91.64%), stick weight (99.20%) and fibre weight ( 96.48%). The high heritability with moderate to high genetic advance over percentage of mean was observed in bark thickness (98.33%, 38.86), stick weight (99.20%, 56.87) and fibre weight (96.48%, 25.02) which indicate preponderance of additive genetic action. Therefore, effective selection would be made considering the stick weight, bark thickness, green weight, plant height and base diameter per plant to produce jute varieties with acceptable yield.